2019
DOI: 10.1002/pat.4578
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polyester/modified mesoporous silica composites for effective bone repair with self‐reinforced properties

Abstract: A series novel composites based on poly(L‐lactide) (PLLA) oligomer modified mesoporous silica (MCM41) homogeneous dispersed into poly(L‐lactide‐co‐trimethylene carbonate‐co‐glycolide) (PLTG) terpolymer has been successfully prepared. The structure of PLTG terpolymer was characterized by 1H NMR. The structure and properties of modified and unmodified MCM41 were attested by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analyzer (TGA), X‐ray diffraction (XRD), N2 adsorption–desorption, scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The TGA curves of MSNs, MSN-SH, MSN-SS-NH2, and MSN-SS-Fc are shown in Figure 3B, clearly indicating the successful modification of the nanoparticles. The initial weight loss of all samples from 50 to 100 °C was due to the physically adsorbed water [24]. Compared to the weight loss of the blank MSNs, the additional weight loss of about 8.72% for MSN-SH was assigned to the removal of the organosilane portion.…”
Section: Resultsmentioning
confidence: 99%
“…The TGA curves of MSNs, MSN-SH, MSN-SS-NH2, and MSN-SS-Fc are shown in Figure 3B, clearly indicating the successful modification of the nanoparticles. The initial weight loss of all samples from 50 to 100 °C was due to the physically adsorbed water [24]. Compared to the weight loss of the blank MSNs, the additional weight loss of about 8.72% for MSN-SH was assigned to the removal of the organosilane portion.…”
Section: Resultsmentioning
confidence: 99%
“…A notable amount of mineralization with a bone shell formation surrounding the bone marrow cavity was observed upon treatment with (G3) confirming the superior osteogenic potential of the dual bioactive factor loaded porous nanofibrous scaffolds. Wang et al (2019) reported the synthesis of poly (L-lactide) (PLLA) oligomer based novel biodegradable polyester modified MSNs for bone tissue repair. Initially, a PLLA-TMC-GA terpolymer (PLTG) was synthesized by ring-opening polymerization at 130°C for 72 h using L-lactide (LLA)/ trimethylene carbonate (TMC)/glycolide (GA) at a ratio of 90:5:5 in the presence of Sn (Oct) 2 as a catalyst.…”
Section: Polymer Functionalized Mesoporous Silica Nanocompositesmentioning
confidence: 99%
“…Similarly, the mechanical property and micropore size of photo‐crosslinked gelatin hydrogel scaffold was also altered by blending MSNs in the preparation process (Wang et al, ). Other types of scaffolds, such as electrospun nanofibers (Mehrasa et al, ; Mehrasa, Asadollahi, Ghaedi, Salehi, & Arpanaei, ; Qiu et al, ), polymer scaffolds (Wang et al, ), elastomers (Li, Guo, Ge, Ma, & Lei, ), and even the 3D‐printed scaffolds (Baumann et al, ; Zhu, Li, Zhu, Zhang, & Ye, ), have also been reported with altered mechanical properties, structures,, or cell–scaffold interactions after doping of MSNs. Besides, MSNs could even regulate the degradation rate of a scaffold.…”
Section: The Diversified Functions Of Msns In Tissue Engineeringmentioning
confidence: 99%